O discurso de Raimundo Nina Rodrigues acerca das religiões africanas na Bahia do século XIX - Serafim, Vanda Fortuna (2010)
In the late nineteenth century, Raimundo Nina Rodrigues started a study about African religions in Bahia. The works produced by this author became milestone of scientific research for the study of the black people in Brazil and produced a pioneering discourse about the African religions.The work of Nina Rodrigues had wide influence on the scientific thinking of the nineteenth and early twentieth century, including about the study of religions, making the understanding of his speech our object of research. Our goal is to think Nina Rodrigues as a product/ producer of a scientific discourse about African religions in Bahia in the nineteenth century, from what looks Rodrigues produces this knowledge and what are the explanatory categories used to refer to African religions in Bahia. The theoretical approach to our research is the History of Ideas, articulating Edgar Morin (2005 c), Bruno Latour (1994) and Michel de Certeau (1982) and their respectives concepts of "complex thinking", "hybrids beings" and "social place". As we recognize that the human subject is included in his object of study and we conceive, inseparably, unity and human diversity, we work with the books "O animismo fetichista dos negros bahianos" (1935) and "Os Africanos no Brasil" (1982), for this, our option for the treatment with the written document is the idea of document/monument by Le Goff (1994). Analysis of the sources, through a thematic approach, had permited us to realize the diversity of thought in Nina Rodrigues, linked to the historical context which he is a product/producer and noted that his work may suffer the action of different schools of thought, not only scientific and the glance by Nina Rodrigues on African religions is a kind of synthesis of social thought of nineteenth, but allied to his personal way of experiencing and understanding the world, even in his religious references and in his relations human.